Novel, promising, and broadband microwave‐absorbing nanocomposite based on the graphite‐like carbon nitride/CuS. Issue 9 (30th August 2019) - Peymanfar, Reza; Karimi, Javad; Fallahi, Reza
ABSTRACT: In this study, a broadband, intense, novel, and promising microwave‐absorbing nanocomposite was prepared using graphite‐like carbon nitride (g‐C3 N4 )/CuS suspended in poly(methyl methacrylate) (PMMA) medium. The g‐C3 N4 nanosheets were synthesized by heating the urea as well as the CuS nanoparticles, and g‐C3 N4 /CuS nanocomposites were prepared using a solvothermal method and then were separately molded by a PMMA solution to investigate their microwave‐absorbing characteristics. The Fourier transform infrared and X‐ray powder diffraction were used to characterize the g‐C3 N4, CuS, and CuS/g‐C3 N4 nanostructures, which confirmed that the pure structure of the nanomaterials has been synthesized. The optical properties of the nanostructures were also investigated by diffuse reflection spectroscopy analysis. Accordingly, the Kubelka–Munk theory suggested significant narrow band gap for g‐C3 N4 /CuS nanocomposite (0.27 eV), facilitating electron jumping and conductive loss. The morphology of the structures was examined using field emission scanning electron microscopy micrographs, illustrating that the uniform hexagonal structures of the CuS nanoplates have been formed and the CuS two‐dimensional structures were uniformly distributed on the g‐C3 N4 nanosheets. Finally, the microwave‐absorbing properties of the CuS, g‐C3 N4, and g‐C3 N4 /CuS were investigated by PMMA as a host. The microwave‐absorbing properties were evaluated using a vector network analyzer. The results illustrated that the maximum reflection loss of the g‐C3 N4 /PMMA nanocomposite was −71.05 dB at 14.90 GHz with a thickness of 2.00 mm, demonstrating a 1.70 GHz bandwidth >30 dB, as well as g‐C3 N4 /CuS/PMMA nanocomposite absorbed 7.30 GHz bandwidth of more than 10 dB with a thickness of 1.80 mm along the x‐ and ku‐band frequency. The obtained results introduced the PMMA as a capable microwave‐absorbing substrate. Besides, the g‐C3 N4 /CuS/PMMA nanocomposite demonstrated metamaterial property and abundant attenuation constant. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48430. Abstract : Microwave absorbing mechanisms of graphite‐like carbon nitride/CuS/PMMA nanocomposite as a novel, broadband, and intense microwave absorber.